2001
DOI: 10.1016/s0735-1097(00)01062-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory norepinephrine treatment of severe autonomic orthostatic hypotension

Abstract: In these selected patients with refractory orthostatic hypotension due to primary autonomic dysfunction, ambulatory norepinephrine infusion therapy has proved to be a promising new therapeutic option. Further long-term studies including more patients are necessary to assess additional indications, reliability and safety of this new method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…After losing the initial beneficial effects of midodrine and fludrocortisone treatment in this patient, we immediately proposed the NE pump infusions given the severity of the symptoms; other drugs such as subcutaneous octreotide, yohimbine, droxidopa, or domperidone may also be considered before proceeding to invasive management as in our patient [1]. This report confirms the results of Oldenburg's study describing six patients successfully treated with the NE pump infusions in which none of them suffered complications due to arterial hypo-or hypertension, or infection of the infusion system [4]. Multi-disciplinary (neurologist/nephrologist/internist/ pharmacologist), expert evaluation, neuro-hormonal assessment data, and blood pressure monitoring are helpful in coping with PAF and assessing the best treatment options, including NE constant infusions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…After losing the initial beneficial effects of midodrine and fludrocortisone treatment in this patient, we immediately proposed the NE pump infusions given the severity of the symptoms; other drugs such as subcutaneous octreotide, yohimbine, droxidopa, or domperidone may also be considered before proceeding to invasive management as in our patient [1]. This report confirms the results of Oldenburg's study describing six patients successfully treated with the NE pump infusions in which none of them suffered complications due to arterial hypo-or hypertension, or infection of the infusion system [4]. Multi-disciplinary (neurologist/nephrologist/internist/ pharmacologist), expert evaluation, neuro-hormonal assessment data, and blood pressure monitoring are helpful in coping with PAF and assessing the best treatment options, including NE constant infusions.…”
Section: Discussionsupporting
confidence: 76%
“…However, in 2001 he presented with progressive worsening of his condition, he was not able to stand up, and eventually he was unable to leave the home. At this time a NE infusion with a portable pump was proposed in the literature and we decided to use it for this patient, after explaining the advantages and the possible risks of that procedure and obtaining his consent during an interdisciplinary meeting [4].…”
Section: Case Reportmentioning
confidence: 99%
“…146 In a recent study of patients with neurogenic OH, it was shown that a precursor of norepinephrine, L-threo-3,4-dihydroxyphenylserine (L-DOPS), could significantly increase both supine and standing BP and improve orthostatic tolerance in all study subjects. Furthermore, these BP increases were closely associated with plasma norepinephrine levels.…”
Section: Sympathomimetic Agents ␣ 1 -Agonistsmentioning
confidence: 99%
“…The majority of clinical trials evaluating the therapeutic effects of these substances were conducted with patients suffering from, mostly neurogenic, orthostatic hypotension [14][15][16]. In mixed samples of persons with chronic and orthostatic hypotension, reductions of subjective symptoms under the sympathomimetic etilefrine were reported [17,18].…”
Section: Introductionmentioning
confidence: 99%